Ekstrak Etanol Daun Eboni Menurunkan Kadar Glukosa Darah Tikus Jantan yang Diinduksi Aloksan (ETHANOLIC EXTRACT OF EBONI LEAF DECREASE BLOOD GLUCOSE LEVEL IN ALLOXAN INDUCED MALE RATS) - Kartini, Khairiah; Khumaidi, Akhmad; Khaerati, Khildah; Ihwan, Ihwam (Jurnal Veteriner, 2018)
Eboni (Diospyros celebica Bakh.) leaf is part of the plant which used on empirically to decrease blood glucose levels. This study aims to knowing the activity of ethanol extract of ebony leaf in decrease blood glucose levels and  the effective dose equivalent to glibenclamide. The study use 25 white rats male (Rattus norvegicus L.) which divided in 5 groups, that is negative control (0.5% NaCMC), positive control (glibenclamide 0.45 mg / kgBW), Etanolic Extarac Eboni Folium (EEDE)  200 mg / kgBW, EEDE 350 mg / kgBW, EEDE 500 mg / kgBW. All groups of white rats were used alloxan induction with dose 140 mg / kgBW intraperitoneal. Three days, after induction, rats with elevated blood glucose levels e”200 mg/dL were treated for 21 days orally. Blood glucose measurement was performed 5 times on days 0, 3, 10, 17, and 24. Blood glucose data was analyzed using One Way ANOVA with 95% confidence level. It is reveled that ebony leaf extract had activity in decrease blood glucose level by alloxan induction method where the effective dose equivalent to glibenclamide was dose 500 mg/kgBW.